Adaptive Nutrient Management for Vegetable Cultivation: A Fuzzy Rule-Based Approach - Pohan, Sry Dhina; Arwani, Muhammad (Jurnal Sistem Cerdas, 2024)
The availability of foodstuffs, especially vegetables in Indonesia, is highly dependent on seasonal changes, making it necessary to implement precision agriculture to improve the efficiency of vegetable cultivation. The accuracy in fulfilling plant nutrient requirements is a key factor in the effectiveness of vegetable cultivation, hence a nutrient solution irrigation control system is essential. The main challenge in developing such a control system is the variation in the duration of nutrient solution irrigation, which is highly dependent on soil fertility levels and the environmental conditions of the vegetable cultivation area. This research proposes a fuzzy rule-based algorithm to determine irrigation duration based on temperature, air humidity, soil moisture, and light intensity. The fuzzy algorithm is implemented in the nutrient solution irrigation control system through a wireless sensor network (WSN). This research resulted in the design of an application for the nutrient solution irrigation control system in vegetable plant growth, capable of determining irrigation duration accurately and clearly with the implementation of the fuzzy rule-based algorithm, resulting in an irrigation duration of 48 seconds/500ml categorized as long for nutrient solution irrigation. The fuzzy rule-based algorithm was tested using Mean Square Error (MAPE) based on the irrigation duration results, yielding an error percentage of 0.25%, which is considered highly accurate in conducting nutrient solution irrigation for vegetable plants. This automated control system has the potential to increase vegetable crop productivity by minimizing fertilizer and water wastage.